Common factors influencing childhood undernutrition and their comparison between Sylhet, the most vulnerable region, and other parts of Bangladesh: Evidence from BDHS 2007–18 rounds - Sanin, Kazi Istiaque; Khanam, Mansura; Rita, Razia Sultana; Haque, Md. Ahshanul; Ahmed, Tahmeed (Frontiers in Nutrition, 2023)
Undernourishment is disproportionately spread within Bangladesh, making some regions like Sylhet more vulnerable than the rest of the country. We aimed to assess the trend of diverse risk factors related to childhood stunting, wasting, and being underweight. Furthermore, we have compared the estimated factors between Sylhet, the most vulnerable region, and other parts of Bangladesh. We performed a secondary data analysis where data were derived from the nationally representative cross-sectional surveys: Bangladesh demographic and health survey (BDHS) 2007, 2011, 2014, and 2017-18 rounds. The outcome variables were childhood undernutrition, including stunting, wasting, and being underweight. Descriptive statistics such as mean, standard deviation, frequency, and proportion were used to summarize the data. All variables were summarized by BDHS survey time points. We used multiple logistic regression models to measure the associated factors with childhood stunting, wasting, and being underweight. The percentage of children under the age of five years who were stunted declined from 40% in 2007 to 31% in 2018. Similar trends are observed in the decrease in the percentage of underweight children, dropping from 39% in 2007 to 22% in 2018. Wasting dropped to 8% in 2018 after years of critically high levels (17%). According to the results of the regression analyses, urban residence, child's age and gender, morbidity, maternal BMI, maternal and paternal education, decision-making ability, use of contraceptives, the occurrence of domestic violence, antenatal care, c-section, and birth interval, as well as geographic region, were all linked to childhood malnutrition. The Sylhet division falls short in several critical risk indicators, including parental education, maternal BMI, obtaining at least four ANC, women's empowerment, and usage of contraceptives. Policymakers must concentrate on region-specific planning and proper intervention to achieve a more uniform improvement across the country.